Konsep Kepemimpinan Negara Menurut Mutakallimîn - Sueb, Musa (TAJDID, 2016)
The concept of nation leadership on Mutakallimîn  (theologians) point of view can be referred to the concept delivered by four well-known schools of theology in Islam: Khawarij, Syi’ah, Mu’tazilah, and Sunni. According to Khawarij, a nation leader recruitment is considered legitimate if it is elected openly and freely. This school of theology allows non-quraisy to be elected. The qualification encompasses power, knowledgeable, fair, modest, religious, and honest. The term (period of time) of leadership shouldn’t be limited. The role of leader (khalifah) according to this school of theology is guiding the people toward the right way based on Islamic teaching (syari’ah). The point of view above is not very much different from that of Syi’ah, another school of theology in Islam. According to Syi’ah, leadership called imamah is not only the system of nation, but also the plan of God. On Syi’ah point of view politics can not be separated from theology. According to Syi’ah a leader (imam) has to be the ancestry of Ali bin Abi Thalib. The role of leader (imam) according to this school of theology is managing the people in order that they are able to gain security and welfare. Another school of theology,  Mu’tazilah has never formed a government. Mu’tazilah believes in the same right of  leadership (imamah). Forming a leadership according to this school of theology is not required by Islamic teaching, but by ratio. The term of leadership is based on the people agreement. The role of leader (imam or khalifah) according to this school of theology is enforcing law, protecting people, taking care of the family, equipping the soldiers with gun, distributing ghanimah and zakat, assigning preachers to the whole country. For Sunni, another school of theology, a leader of nation is called khilafah or imam. Previously, this school of theology thought that a leader has to be the ancestry of quraisy and be based on the practice conducted by the prophet’s disciples in the early Islam. Later, Sunni applies convention (syura) and justice. According to Abu Zahra, Sunni’s political paradigm has four main principles: the importance of ancestry, oath (baiat), convention (syura), and justice. For that reason the term of leadership, according to Sunni, should be based on a convention. The role of leader (khilafah or imam) according to this school of theology is applying the four principles.